Ion Selective Poly(vinyl) chloride Membrane Electrode for the Determination of Dapoxetine Hydrochloride in Tablets - Aljazzar, Samar O. (Asian Journal of Pharmaceutics (AJP), 2017)
Aim: To fabrication and characterization of liquid membrane ion selective electrode for the determination of dapoxetine (DAP) in pure form and in tablets. Materials and Methods: The membranes compositions were studied by varying the percentages (w/w) of the ion-pair, poly(vinyl) chloride (PVC) and dioctyl phthalate (DOP) until an optimum composition was obtained based on its performance characteristics. The membranes of 0.4-mm thickness were glued to one end of a Pyrex glass tube by careful removal from the glass plate. The electrode was filled with a mixture of 10−2 mol/L NaCl and 10−2 mol/L DAP as an internal filling solution and then preconditioned by soaking in 10−3 mol/L DAP for 3 h before use. Results and Discussion: A new DAP ion-selective PVC membrane electrode was fabricated based on the use of DAP-phosphomolybdate as the electroactive substance, and DOP as the plasticizing agent. The performance characteristics of the electrode were evaluated according to IUPAC recommendations reveal a fast, stable and linear response over the concentration range 2.0 × 10−5–1.0×10−2 mol/L for DAP. The electrode was successfully applied to the determination of DAP hydrochloride in pure solutions and in tablets by standard addition potentiometry. Conclusion: The proposed electrode is sufficiently simple and selective for the determination of DAP hydrochloride in pure form and pharmaceutical preparations. This electrode is sensitive and accurate to be a privilege for applications in DAP HCl determination and its quality control.